Familia aniztasunaren trataera Haur Hezkuntzako ikasgeletan: irakasleen aurreiritziak eta eskoletako materiala - Alize Olazar Intxausti; Nahia Idoiaga Mondragon (Ikastorratza.e-Revista de Didáctica, 2022)
Childhood Education classrooms in the Basque Autonomous Community. For this purpose, a questionnaire was sent to 178 teachers and students of Early Childhood Education Degree. The results indicate that in spite of framing family diversity within the teaching plan, and knowing the family reality of the schools, there are few materials and references to work on multiple family models in the classrooms. In addition, teachers have expressed quite progressive ideas about family diversity, although there are several differences between active teachers and undergraduate students. Finally, the teachers point out that despite the importance of working on family diversity, they have not received enough training in the subject, so the challenges that this situation can generate will be analyzed so that the school can make an inclusive treatment of families, proposing its integration in the activity of the Early Childhood Education classrooms.